Aspects of Personal Security of Polish and Austrian Employees Through Lens of Crisis Management - Ewa MATUSKA; Joanna GRUBICKA (Communications of International Proceedings, 2022)
The article presents an analysis of quantitative research carried out on a sample (N = 163) of Polish and Austrian employees using direct testing method of subjective assessment of the sense of security and its components. Statistical analysis using the chi-square test revealed that both Polish as Austrian employees despite of the coronavirus crisis situation assess their personal security at the similar level although there exist also minor differences btw both national groups which probably reflecting differences in pandemics crisis management approaches of the governments of Poland and Austria. The obtained data have to be treated as a pilot study that should be continued on a wider group of respondents. In conclusions is stressed the importance of prudent anti-crisis policies and thoughtful crisis management strategies.
Keywords: personal security; employees; Polish and Austrian employees; crisis management